PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP EKUITAS DANA (Survey Pada Kabupaten/Kota Se-Sulawesi Tengah) - Yulianto Gagaramusu, Yusran (Katalogis, 2015)
The research aims to explore and analyze simultaneous and partial effects of local revenue, general allocation fund, and special allocation fund on fund equity. The sample consists of 11 regencies/cities in Central Sulawesi that is taken by using nonprobability sampling technique, The method of analysis is descriptive with multiple linier regressions analysis. The results show that the growth of local revenue in 3-year budget is higher than the growth of general allocation fund, special allocation fund and fund equity. Simultaneous test indicates that local revenue, general allocation fund and special allocation fund have positive and significant effects on fund equity. Partial test shows that local revenue, general allocation fund, and special allocation fund partially have significant effects on fund equity in 11 regencies/cities in Central Sulawesi. Coefficient determinant with Adjusted R-Square value of 0,361 shows that 36,10% of fund equity is affected by local revenue, general allocation fund, and special allocation fund,while the remaining value of 63,90% is affected by other variables that are not examined in this study.